Synergistic antibacterial activity of monoterpenes in combination with conventional antimicrobials against Gram-positive and Gram-negative bacteria - Pereira de Lira, Maria Helena; Fernandes Queiroga Moraes, Gustavo; Macena Santos, Girlene; Patrício de Andrade Júnior, Francisco; de Oliveira Pereira, Fillipe; Oliveira Lima, Igara (Revista de Ciências Médicas e Biológicas, 2020)
Introduction: bacterial infections are a public health problem. Besides, the emergence of strains resistant to antimicrobials has contributed to the search for new alternatives, such for the terpenes with antimicrobial potential. Objectives: the objective of this study was to determine the possible interaction of isolated monoterpenes (-)-Carveol, Geraniol, Citronellol, α-terpineol, R-(-) Carvone, (-)-Menthol, Linalool, D-Dihydrocarvone, and (-)-Terpine-4-ol with conventional antimicrobials (Chloramphenicol, Minocycline, Amoxicillin and Ciprofloxacin) when they are evaluated on Staphylococcus aureus, Staphylococcus epidermidis, Bacillus subtilis, Escherichia coli and Pseudomonas aeruginosa strains. Methodology: the minimum inhibitory concentrations of these test drugs were determined using the microdilution method. The Checkerboard method was used to assess the interactions, by determining the fractional inhibitory concentration index (FIC index). Results: aamong the monoterpenes, only Carveol, Citronellol, and Geraniol presented antimicrobial activity (MIC < 1024 μg/mL). They presented synergistic effects against Pseudomonas aeruginosa ATCC-9027 (FIC index ≤ 0.5) when in combination with Minocycline. Conclusion: this study contributes to the development of new approaches to control bacterial resistance and to the possibility of discovering new drugs.